Agreement of Immunoassay and Tandem Mass Spectrometry in the Analysis of Cortisol and Free T4: Interpretation and Implications for Clinicians - Rochelle E. Tractenberg; Jacqueline Jonklaas; Steven J. Soldin (International Journal of Analytical Chemistry)
Objective. To quantify differences in results obtained by immunoassays (IAs) and tandem mass spectrometry (MSMS) for cortisol and free thyroxine (FT4). Design & Patients. Cortisol was measured over 60 minutes following a standard ACTH stimulation test (n=80); FT4 was measured over time in two cohorts of pregnant (n=57), and nonpregnant (n=28) women. Measurements. Samples were analyzed with both IA and MSMS. Results. Results for cortisol by the two methods tended to agree, but agreement weakened over the 60-minute test and was worse for higher (more extreme) concentrations. The results for FT4 depended on the method. IA measurements tended to agree with MSMS measurements when values fell within “normal levels”, but agreement was not constant across trimester in pregnant women and was poorest for the extreme (low/high) concentrations. Correlations between MSMS measurements and the difference between MSMS and IA results were strong and positive (0.411<  r  <0.823; all P<.05). Conclusions. IA and MSMS provide different measures of cortisol and FT4 at extreme levels, where clinical decision making requires the greatest precision. Agreement between the methods is inconsistent over time, is nonlinear, and varies with the analyte and concentrations. IA-based measurements may lead to erroneous clinical decisions.